Wheat diseases and their management in Karnataka- An overview - Kalappanavar, Ishwar Kenchappa (Journal of Cereal Research, 2012)
Wheat crop in India, owing to its diverse climatic conditions prevailing throughout the country, suffers more or less due to all three rusts. Among the major constraints of limiting the wheat production in Karnataka is leaf rust fallowed by leaf blight and foot rot in the rain fed ecosystems. In Karnataka several workers have made an attempt to study the wheat diseases and their spread, mechanism of infection, loss due to individual diseases, and mechanism of resistance, epidemiological factors and management aspects. In the present work it has been tried to compile the work which has been done in Karnataka till date so that people can very easily trace the track at one look.